Reciprocal association between voting and the epidemic spread of COVID-19: observational and dynamic modeling study. (25th September 2021) - Zeitoun, Jean-David; Faron, Matthieu; Manternach, Sylvain; Fourquet, Jérôme; Lavielle, Marc; Lefèvre, Jérémie H
Abstract: Background: Whether voting is a risk factor for epidemic spread is unknown. Reciprocally, whether an epidemic can deter citizens from voting has not been often studied. We aimed to investigate such relationships for France during the coronavirus disease 19 (COVID-19) epidemic. Methods: We performed an observational study and dynamic modelling using a sigmoidal mixed effects model. All hospitals with COVID-19 patients were included (18 March 2020–17 April 2020). Abstention rate of a concomitant national election was collected. Results: Mean abstention rate in 2020 among departments was 52.5% ± 6.4% and had increased by a mean of 18.8% as compared with the 2014 election. There was a high degree of similarity of abstention between the two elections among the departments ( P  < 0.001). Among departments with a high outbreak intensity, those with a higher participation were not affected by significantly higher COVID-19 admissions after the elections. The sigmoidal model fitted the data from the different departments with a high degree of consistency. The covariate analysis showed that a significant association between participation and number of admitted patients was observed for both elections (2020: β = –5.36, P  < 1e −9 and 2014: β = –3.15, P  < 1e −6 ) contradicting a direct specific causation of the 2020 election. Participation was not associated with the position of the inflexion point suggesting no effect in the speed of spread. Conclusions: Our results suggest that the surrounding intensity of the COVID-19 epidemic in France did not have any local impact on participation to a national election. The level of participation had no impact on the spread of the pandemic.